2018
DOI: 10.1038/s41375-017-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

PI3K orchestration of the in vivo persistence of chimeric antigen receptor-modified T cells

Abstract: In vivo persistence of chimeric antigen receptor (CAR)-modified T cells correlates with therapeutic efficacy, yet CAR-specific factors that support persistence are not well resolved. Using a CD33-specific CAR in an acute myeloid leukemia (AML) model, we show how CAR expression alters T cell differentiation in a ligand independent manner. Ex vivo expanded CAR-T cells demonstrated decreased naïve and stem memory populations and increased effector subsets relative to vector-transduced control cells. This was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 44 publications
3
137
0
1
Order By: Relevance
“…Excitingly, genome‐editing technologies including clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) and transcription activator‐like effector nucleases (TALEN) may further refine AML CART cell specificity, potency, and prolonged persistence, at the same time reducing “off target” effects . Preclinical studies combining CART therapy with specific kinase inhibitors: CD19 CAR T and ibrutinib in ALL, FLT3 CART with crenolanib in AML, and CD33 or CD19 CAR T cells with PI3K inhibitor LY294002 in AML and ALL, respectively, are underway . Recently, CD4+ and CD8+ HA‐1 T‐cell receptor (TCR) T cells has been studied in a phase I trial for treating HLA‐A*0201 HA‐1‐positive patients with R/R acute leukemia including AML (NCT03326921).…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…Excitingly, genome‐editing technologies including clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) and transcription activator‐like effector nucleases (TALEN) may further refine AML CART cell specificity, potency, and prolonged persistence, at the same time reducing “off target” effects . Preclinical studies combining CART therapy with specific kinase inhibitors: CD19 CAR T and ibrutinib in ALL, FLT3 CART with crenolanib in AML, and CD33 or CD19 CAR T cells with PI3K inhibitor LY294002 in AML and ALL, respectively, are underway . Recently, CD4+ and CD8+ HA‐1 T‐cell receptor (TCR) T cells has been studied in a phase I trial for treating HLA‐A*0201 HA‐1‐positive patients with R/R acute leukemia including AML (NCT03326921).…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…Jetani and colleagues recently reported that the FLT3 inhibitor crenolanib had a synergist activity with FLT3-directed CAR T cells in a FLT3-ITD AML model, at least in part by increasing FLT3 surface expression (79), and similar results were also presented for midostaurin (80). Besides, it was recently reported that PI3K inhibition can enhance CD33-directed CAR T cells durability, thus improving antitumor activity (81).…”
Section: Car T Cells For Myeloid Diseasesmentioning
confidence: 85%
“…4-1BB, ICOS [75]; 6) altered metabolism status [76,77]. These potentially persistent tumor specific T cells could control cancer and prevent recurrence for a long time [78,79].…”
Section: The Influence Of Immunosuppressive Tumor Microenvironment (Tmentioning
confidence: 98%